IMPLEMENTASI HIDDEN CURRICULUM PADA KEGIATAN LATIHAN DASAR KEPEMIMPINAN SISWA (LDKS) DI SEKOLAH MENENGAH ATAS - Teresiany Wulan Gultom (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the implementation of hidden curriculum in Basic Student Leadership Training (LDKS) activities in Senior High Schools (SMA). Hidden curriculum refers to learning that is not listed in the formal curriculum, but plays an important role in the formation of students' character and values, such as attitudes, behaviors, and norms. This study uses a qualitative approach with Husserl's phenomenological theory to understand the participants' experiences and perspectives related to the implementation of the hidden curriculum. Data were collected through in-depth interviews with teachers, facilitators, and students involved in LDKS activities. The results show that the implementation of the hidden curriculum in LDKS is still inconsistent, with differences in understanding of this concept among facilitators and teachers. In addition, the lack of evaluation of the effectiveness of the hidden curriculum and the existence of conflicts between the formal curriculum and the hidden curriculum are obstacles in achieving the goal of optimal character education. The findings also show that the involvement of all parties, including parents and the community, is minimal in this process. Therefore, this study suggests the need to increase understanding of the hidden curriculum, develop a more structured evaluation system, align the formal curriculum and the hidden curriculum, and increase the involvement of all parties to increase the effectiveness of the implementation of the hidden curriculum in LDKS activities in high schools.